In vitro characterization of Trichophyton rubrum biofilm by combined anti-biofilm enzymes - Amna Rehman; Fatima Ismail; Ayesha Safdar; Muhammad Imran (PLoS ONE, 2025)
Trichophyton rubrum, a dermatophyte, demonstrates a notable ability to form mature biofilms on skin and associated surfaces, strengthening its resistance to antifungal agents. This characteristic poses intricate challenges in dermatological research and therapeutic strategies, underscoring the need for innovative approaches to effectively manage fungal infections. This work assessed the impact of the anti-biofilm enzymes, i.e., cellulase, protease, and amylase, individually and in combination, on the eradication and inhibition of T. rubrum biofilm. After 168 hours of incubation, T. rubrum biofilm formation matured, and the anti-biofilm enzymes significantly reduced the rate of biofilm development. The rates of biofilm inhibition and eradication for cellulase, protease, and amylase were 64%, 38%, and 28% at 72 hours of incubation, and 47%, 25.87%, and 17%, respectively, at 168 hours. However, the combined anti-biofilm enzymes (cellulase, protease, and amylase) had a 60.62% biofilm suppression rate. SEM analysis revealed marked reductions in T. rubrum conidial density, disrupted hyphal structures, and diminished biofilm adherence in enzyme-treated samples compared to untreated controls, visually supporting the inhibitory effect observed in quantitative assays. These morphological alterations indicate compromised fungal viability and structural disintegration of the biofilm matrix. Collectively, the SEM findings reinforce the therapeutic potential of enzyme-based strategies against dermatophytic biofilms. Additionally, these anti-biofilm enzymes have shown strong efficacy in reducing the exopolysaccharide (EPS) content and degrading the complex EPS matrix network. The T. rubrum biofilm treated with anti-biofilm enzymes, such as cellulase and protease, resulted in EPS degradation by FTIR analysis. The antibiofilm enzyme cellulase showed notable degradation of the beta 1–4 linkage within the glycosidic bond. A significant degradation is observed when T. rubrum biofilm is treated with combined enzymes (cellulase, protease, and amylase). The combined enzymatic treatment disrupted the EPS matrix, indicating its potential as an effective strategy for inhibiting biofilm formation by T. rubrum.